Hybrid Flexible in Teaching English at Junior High School in Post Pandemic Era - Patimah, St.; Sahril, Sahril; Aeni, Nur (BATARA DIDI : English Language Journal, 2024)
This research was designed to investigate hybrid flexible in teaching English. There were 32 students participated in this research by using the purposive sampling method. This mixed-methods study looked into the hybrid flexible method implemented in teaching English, the benefits of using hybrid flexible method and the challenges of applying hybrid flexible. A structured interview, observation and a questionnaire were used to gather the data. According to the findings of the study, the majority of students are able to enhance their English vocabulary with the aid of hybrid learning that is adaptable to their needs. Students find hybrid learning to be highly beneficial since it helps them gain new language and improve their vocabulary abilities. The flexible hybrid learning method makes learning enjoyable and provides students with access to a variety of sources of information, particularly the Internet. The student must be able to use the technology needed to access the content or course, as face-to-face and online learning will be required. These strategies are quite beneficial for students since they assist them in learning a new language or expanding their vocabulary. Aside from that, the findings of this study will be of great assistance to educators who seek to use this method in the classroom to improve the academic performance of their students, particularly in the post-pandemic era.